Status and factors influencing on-farm conservation of Kam Sweet Rice (Oryza sativa L.) genetic resources in southeast Guizhou Province, China - Yanjie Wang; Aixia Jiao; Huicha Chen; Xiaoding Ma; Di Cui; Bing Han; Renchao Ruan; Dayuan Xue; Longzhi Han (BMC, 2018)
Abstract Background Kam Sweet Rice (KSR) is a special kind of rice landrace that has been cultivated for thousands of years in the borders of Guizhou, Hunan, and Guangxi Provinces of China, and is mainly distributed in southeast Guizhou Province of China currently. KSR has many unique qualities, including strong resistance to diseases, pests, and adverse abiotic conditions, difficulty of threshing, and well glutinous features. KSR germplasm resources are an indispensable material and cultural symbol in the production and daily life and customs of the Dong people. Related studies showed that numerous traditional KSR varieties and cultivation area of KSR decreased sharply from the Qing dynasty to 2015, but many KSR varieties are still conserved in Dong villages of southeast Guizhou Province compared to other areas. However, the number of KSR varieties that are conserved on farms in southeast Guizhou Province and factors influencing the erosion and conservation of KSR genetic resources is unclear. Therefore, this study was an on-farm conservation investigation of KSR genetic resource in China's major KSR producing areas-Liping, Congjiang, and Rongjiang counties in Guizhou Province and influencing factors analysis of KSR abandonment and conservation. Methods The information of KSR conservation status and variety characteristics, typical villages, Dong's cultural customs, and factors influencing KSR abandonment and conservation was obtained using ethno-biology methods, mainly through field research interviews, including participatory observation, semi-structured interviews, key informant interviews, focus group discussions, and cultural anthropology. The altitude, plant height, awn color and length, hull color, and rice color of 156 KSR accessions in 28 villages were recorded. The variety quantity and cultivation area of KSR were investigated in 33 ethnic villages. Questionnaire surveys were conducted in typical Dong villages to obtain local farmers' attitudes toward cultivation and protection of KSR. We randomly selected 26 farmers from Sizhai village and 30 farmers from Huanggang village and chose 3 social characteristics including age, gender, and education levels of farmers, and adopted the method of face-to-face interviewing to complete the questionnaires. Then, we analyzed the correlation and determined the significance between farmers with different social characteristics and farmers' attitudes to KSR development and protection using SPSS 17.0 software. Results (1) On-farm conservation status of KSR: a total of 156 KSR varieties were collected from 28 ethnic minority villages from 13 townships (accounting for 21% of three counties) in Liping, Congjiang, and Rongjiang counties. KSR accessions accounted for more than 90% of local rice varieties in each village. According to local farmers, although the quantity of KSR varieties decreased more than 50% in the investigated villages compared to the past 10-20 years, some Dong villages have still cultivated KSR, accounting for more than 50% of the rice field area in 10 villages. This result showed that many KSR varieties are still conserved by in Dong villages, and these KSR varieties have a high genetic diversity of phenotypes. (2) Typical villages investigation: the cultivation area of KSR in Congjiang was the highest, 6.7 times larger than Liping and eight times larger than Rongjiang. In addition, the cultivation area of KSR in Dong villages was larger than that in other ethnic villages, and villages that had a higher planting area of KSR had more KSR accessions. (3) Farmers' attitude toward the development and conservation of KSR: Dong farmers hold the negative attitudes concerning the development of KSR resources, but they thought it is necessary to protect KSR landraces. Especially, a high level of education and female, young, and old farmers played more important roles in the cultivation and protection of KSR. Conclusions Until now, some Dong ethnic villages have still cultivated KSR for thousands of years in Qiandongnan area, although the number of varieties and the planting area of KSR have been greatly reduced. In addition, ethnic traditional culture and social customs were the main influencing factors of KSR conservation; economic, management, and policy factors were the main influencing factors of KSR abandonment. Through the analysis of the correlation between farmers with different social characteristics and their attitudes toward the cultivation, reasons for conservation and abandonment, development tendency, and protection of KSR, we found that a high level of education and female, young, and old farmers play more important role in the cultivation and protection of KSR. Therefore, in order to promote the protection and sustainable utilization of KSR, it is necessary to build on-farm conservation of KSR and improve the position of female farmers and the education level of young people, and encourage the old people to educate the middle-aged to conserve and protect KSR as well as Dong's traditional culture and social customs. This study is of great significance to promote better protection and optimal utilization of KSR and enable the public, government, and related researchers pay more attention to conserving ethnic traditional cultures.